Role of vascular ultrasound in cases of lower limb hyperpigmentation - Himanshu Kumar; P K Sharma; U C Garga (Wolters Kluwer Medknow Publications, 2019)
Background: Hyperpigmentation remains an important finding in cases of venous insufficiency and peripheral arterial disease (PAD) among the vascular causes. Aims: This study aimed at finding the presence of arterial and/or venous insufficiency in patients of lower leg hyperpigmentation by using vascular ultrasound (US). Materials and Methods: Fifty patients of lower leg pigmentation were included in the study. The detailed history, general physical examination, and laboratory investigations were done. Color Doppler ultrasonography was performed to check for venous insufficiency/PADs. Qualitative variables were correlated using chi-square test/Fisher's exact test. P < 0.05 was considered statistically significant. Results: The mean age of the patients was 44.32 ± 14.16 years. Four patterns of skin changes were seen - reticulate macular, diffuse macular, lipodermatosclerosis and ulcer. Thirty-five (70%) patients had no visible varicose vein while 15 (30%) had visible varicose vein. In patients with visible varicose vein, color Doppler showed signs of venous insufficiency in all patients, but in cases of no visible varicose vein, color Doppler showed signs of venous insufficiency in 19 (54.28%) patients and showed no signs of venous insufficiency in others (P = 0.78). Only 1 (2%) patient showed atherosclerotic changes in both anterior tibial arteries. Conclusion: All patients with lower leg pigmentation with or without visible varicose vein should undergo vascular US to rule out any venous insufficiency.